Properties of phosphatidate phosphohydrolase and diacylglycerol acyltransferase activities in the isolated rat heart. Effect of glucagon, ischaemia and diabetes - Schoonderwoerd, K; Broekhoven-Schokker, S; Hülsmann, W C; Stam, H (Biochemical journal, 1990)
Myocardial triacylglycerol hydrolysis is subject to product inhibition. After hydrolysis of endogenous triacylglycerols, the main proportion of the liberated fatty acids is re-esterified to triacylglycerol, indicating the importance of fatty acid re-esterification in the regulation of myocardial triacylglycerol homoeostasis. Therefore, we characterized phosphatidate phosphohydrolase (PAP) and diacylglycerol acyltransferase (DGAT) activities, enzymes catalysing the final steps in the re-esterification of fatty acids to triacylglycerols in the isolated rat heart. The PAP activity was mainly recovered in the microsomal and soluble cell fractions, with an apparent Km of 0.14 mM for both the microsomal and the soluble enzyme. PAP was stimulated by Mg2+ and oleic acid. Oleic acid, like a high concentration of KCl, stimulated the translocation of PAP activity from the soluble to the particulate (microsomal) fraction. Myocardial DGAT had an apparent Km of 3.8 microM and was predominantly recovered in the particulate (microsomal) fraction. Both enzyme activities were significantly increased after acute streptozotocin-induced diabetes, PAP from 15.6 +/- 1.1 to 28.1 +/- 3.6 m-units/g wet wt. (P less than 0.01) and DGAT from 2.23 +/- 0.11 to 3.01 +/- 0.11 m-units/g wet wt. (P less than 0.01). In contrast with diabetes, low-flow ischaemia during 30 min did not affect PAP and DGAT activity in rat hearts. Perfusion with glucagon (0.1 microM) during 30 min did not affect total PAP activity, but changed the subcellular distribution. More PAP activity was recovered in the particulate fraction. DGAT activity was lowered by glucagon treatment from 0.37 +/- 0.03 to 0.23 +/- 0.02 m-unit/mg of microsomal protein (P less than 0.05). The role of PAP and DGAT activity and PAP distribution in the myocardial glucose/fatty acid cycle is discussed.